Development of high damping natural rubber/butyl rubber composites compatibilized by isobutylene-isoprene block copolymer for isolation bearing - J-C. Li; H-S. Zhang; X-Y. Zhao; J-G. Jiang; Y-X. Wu; Y-L. Lu; L-Q. Zhang; T. Nishi (eXPRESS Polymer Letters)
Natural rubber (NR) and butyl rubber (IIR) blends were compatibilized by isobutylene-isoprene block copolymer (IIBC) which was specifically synthesized with a relatively high content of isoprene (14.5% mole fraction). Aiming at high damping elastomers, the IIR acts as the high damping phase dispersed in the natural rubber (NR) matrix in this blend. The morphology and microstructure was characterized by atomic force microscope (AFM) and transmission electron microscope (TEM). The results indicated that the IIBC as a compatibilizer could greatly increase the interfacial thickness. Damping property was studied by dynamic mechanical thermal analyzer (DMTA) and rubber processing analyzer (RPA). The results showed that the loss factor greatly increased with adding IIBC, and this may be due to the improved stress transfer promoting the IIR phase to deform and then dissipate energy. The tensile test demonstrated that the tensile strength and modulus increased when 4 parts per hundred rubber [phr] of IIBC was added. Finally, the NR and new NR/IIR isolation bearing samples were prepared and tested on a pressure shear testing machine that could simulate the actual situation during an earthquake.The results showed that hysteretic loss (for one cycle) of the new NR/IIR sample is 83% higher than that of the NR sample, rendering the compatibilized blends potential in isolation rubber bearings application.